Bologna Process within the Italian University - Luigi Binanti (Universidad Nacional de Educación a Distancia (UNED), 2009)
This paper exposes the Italian reform of higher education beginning from the ministerial law of 1999 and put really in practice in the Italian university since 2001. The structure of the university, the different types from courses, doctorate and agencies of established evaluation and advising are explained, as well others decrees concerning documents, specially the supplement to diploma.Later the article analyzes the reality of the change in the higher Italian education and presents the difficulties due on the one hand to the increase of the demand of higher education in the country and by another one to the economic difficulties motivated by the budgetary limitations and the little tradition of the Italian university with respect to the diversification of the financing sources.The author comments next the change about the methodology and the difficulties and contradictions between the model proposed by the process of Bologna and the reality of the university students in whom the profile has changed and in its majority not rather deals with students oftwenty years dedicating full time to yours studies but the students that at the sametime works and adult people who have arrived after the university.Referring to structure of degrees, he comments the difficulty that has had to happen of the traditional Italian structure of «laurea quatriennale» tofirst cycles of three years in which in many occasions the studies have been compacted that previously lasted four years. Next to this, the diversity ofthe academic offerin the Masters with a great freedom on the part of the universities make something difficult to future financing of these studies and their viability in the different universities.Finally it refers how the implantation of system ECTS has benefited mobility in the Italian university when facilitating specially equivalences between the European universities and consequently to assure to the student the taking in consideration from the work made in its period mobility.The article ends annexed a terminological one with respect to used the organizational and educational vocabulary in him himself. El presente artículo expone la reforma italiana de la enseñanza superior iniciada a partir del decreto ministerial de 1999 y puesta en práctica realmente en la universidad italiana a partir del 2001. Se explica la estructura de la universidad, los diferentes tipos de cursos, de doctorado y de agencias de evaluación y asesoramiento establecidos, así como los decretos referidos a documentos, especialmente el suplemento al título. Posteriormente el artículo analiza la realidad del cambio en la educación superior italiana y constata las dificultades debidas por una parte al incremento de la demanda de educación superior en el país y por otra a las dificultades económicas motivadas por las limitaciones presupuestarias y por la escasa tradición de la universidad italiana respecto a la diversificación de las fuentes de financiación. Después se comenta la realidad del cambio a nivel didáctico, indicándose las dificultades y contradicciones entre el modelo propuesto por el proceso de Bolonia y la realidad de los estudiantes universitarios en los que el perfil ha cambiado y en su mayoría no se trata de estudiantes de veinte años dedicándose a sus estudios a tiempo completo sino más bien de estudiantes que al mismo tiempo trabajan y de personas adultas que han llegado con posterioridad a la universidad. En el ámbito estructural, se comenta la dificultad que ha habido para pasar de la tradicional estructura italiana de «laurea quatriennale» a unos primeros ciclos de tres años en los que en muchas ocasiones se han compactado los estudios que anteriormente duraban tres años. Junto a esto, la diversidad de la oferta formativa de los segundos ciclos (masters) con una gran libertad por parte de las universidades, dificulta en gran medida la financiación futura de estos estudios y su viabilidad en las diferentes universidades. Finalmente refiere cómo la implantación del sistema ECTS ha beneficiado la movilidad en la universidad italiana al facilitar especialmente las equivalencias entre las universidades europeas y en consecuencia asegurar al estudiante la toma en consideración del trabajo realizado en su período de movilidad. El artículo acaba con un anexo terminológico respecto al vocabulario organizativo y docente utilizado en el mismo.